1999
DOI: 10.1016/s0091-6749(99)70367-2
|View full text |Cite
|
Sign up to set email alerts
|

Syk deficiency in nonreleaser basophils☆☆☆★

Abstract: The absence of detectable Syk could explain the nonreleaser phenotype of basophils from some donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
132
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(140 citation statements)
references
References 14 publications
6
132
1
1
Order By: Relevance
“…Previous investigators established that Fc⑀RI expression and subunit composition are normal in nonreleaser basophils (3,5). We found that basophils from three nonreleaser donors lacked detectable levels of the Fc⑀RI-associated protein tyrosine kinase, Syk (6). Remarkably, Syk levels were normal in B cells, eosinophils, and neutrophils from the same donors.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…Previous investigators established that Fc⑀RI expression and subunit composition are normal in nonreleaser basophils (3,5). We found that basophils from three nonreleaser donors lacked detectable levels of the Fc⑀RI-associated protein tyrosine kinase, Syk (6). Remarkably, Syk levels were normal in B cells, eosinophils, and neutrophils from the same donors.…”
mentioning
confidence: 62%
“…Reactions were terminated by dilution in ice-cold PBS and centrifugation, and histamine in cell pellets and supernatants was measured using an RIA (Alpco, Windham, NH), as described (6,8). Total histamine was measured in supernatants obtained by freeze thawing cell aliquots in PBS/ EDTA, followed by centrifugation at 10,000 ϫ g for 5 min to remove debris.…”
Section: Histamine Releasementioning
confidence: 99%
See 2 more Smart Citations
“…The absence of Syk expression led peripheral blood basophils to fail to degranulate in response to cross-linking the high affinity IgE receptor Fc⑀ receptor I (41). Also, TB1A2 cells, a Syk-negative variant of basophilic leukemia RBL-2H3 cells, failed to release histamine by the cross-linking system (22).…”
Section: Discussionmentioning
confidence: 99%